Load to failure analysis of short segment pedicle screw instrumentation with screw at the fracture level in unstable thoracolumbar burst fracture ; an animal biomechanical study - Abdul Hamid, Othman (2014)

(untitled)
INTRODUCTION Thoracolumbar fracture is the most common spinal fractures worldwide. Despite this, the indications and the methods of treatments remain controversial. The short segment pedicle screw instrumentation with the addition of screw at the fracture level has been shown in biomechanical and clinical studies to have promising results with its performance and outcome. This study looks at the biomechanical properties of this construct when being loaded maximally in compression comparing it to the conventional long segment fixation. METHODOLOGY This experimental biomechanical study is performed using 8 cow spines. Unstable burst fracture is firstly induced and the spines are randomly divided into two groups. First group is instrumented with the short segment pedicle screw with the addition of intermediate screw and the second group is the long segment construct. The constructs are loaded in compression using the Instron 8874 material testing machine and the values of strength and maximum load obtained are recorded. The mechanism of failures are also analyzed. Data was analyzed using SPSS version 20. RESULTS The means of the strength was 4248.6 N in the short segment group whilst the long segment recorded a means of 4085.4N. The compressive load was 0.7550 MPa and 1.060 MPa for the short and long segment respectively. However no significant difference between these two groups were found with p=0.686 and p=0.486 for strength and compression respectively. The method of failure was screw pullout for both groups. CONCLUSION The short segment pedicle screw instrumentation with the addition of intermediate screw have similar load to failure compared to the long segment fixation. In both groups the construct fail by screw pullout.